Clinical characteristics and outcome of dogs with presumed primary renal lymphoma. (31st July 2019) - Taylor, A.; Finotello, R.; Vilar‐Saavedra, P.; Couto, C. G.; Benigni, L.; Lara‐Garcia, A.
Abstract : Objectives: To characterise the presentation, clinicopathologic data and outcome of 29 dogs with presumed primary renal lymphoma. Materials and Methods: Retrospective analysis of medical records of dogs with suspected primary renal lymphoma from 11 institutions. Results: All dogs were substage b, and lethargy and gastrointestinal signs were common presenting complaints, as were azotaemia (n=25; 86%) and erythrocytosis (n=15; 51%) on biochemical testing. Ultrasonography typically revealed bilateral renal lesions (n=23; 79%), renomegaly (n=22; 76%) and abdominal lymphadenopathy (n=14; 48%). Chemotherapy was the only treatment in 23 dogs, of which 11 responded, all considered partial responses. For all dogs the median progression‐free survival and median overall survival times were 10 days (range: 1 to 126) and 12 days (range: 1 to 212), respectively, and for dogs that responded to chemotherapy 41 days (range: 10 to 126) and 47 days (range: 10 to 212), respectively. Clinical Significance: Primary renal lymphoma in dogs appears to be associated with a poor prognosis and short‐lived response to chemotherapy.